Milk quality as a function of temperature-cycled, reduced-fat milk stored in various size containers - L.F. Julstron; Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 2006)
Packaged, reduced-fat milk was subjected to a 20 min/day temperature cycle during a 7-day refrigeration period to determine the effect on milk quality. Temperature cycling did not affect the compositional or microbial counts in reduced-fat milk stored in various package sizes. Analysis of headspace compounds during the 7 days of storage, however, showed that benzaldehyde, 2-butanone, 2-heptanone, hexanal, and octanal concentrations significantly changed, indicating that milk flavor was altered. Concentration of heptanal, a compound associated with lipid oxidation, was higher in milk packaged in half-gallon and 1-gallon containers, compared; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; Milk flavor; Packaging size; Temperature cycling